Monetary policy shocks in an economy with segmented markets - Filippo Occhino (Rutgers University, Department of Economics, 2001)
After a contractionary monetary policy shock, aggregate output decreases over time with a trough after a year and a half, while the real interest rate increases immediately, and remains high for about three quarters. A central step in the explanation is obtaining a persistent increase in the real interest rate, holding aggregate output constant. I study an endowment economy with segmented markets, where, as in the U.S. economy, monetary policy is set in terms of a short-term nominal interest rate, and I show that the real interest rate increases sizeably for up to one year. The shock has a liquidity effect, moving money and interest rates in opposite directions. The endogenous processes for the money growth rate and the real interest rate are strongly serially correlated and close to their empirical counterparts. The more segmented are markets, the stronger and more persistent are the effects of monetary policy shocks, and the higher is the serial correlation of the processes for the money growth rate and the real interest rate. Economies where the intertemporal elasticity of substitution is low exhibit the same qualitative behavior as economies where the market segmentation is high.
Keywords: E52; 330; segmented markets; Geldpolitik; Schock; Liquiditätseffekt; Marktsegmentierung; Realzins; Theorie